Omphaloprenol A: a new bioactive polyisoprenepolyol isolated from the mycelium of poisonous mushroom Omphalotus japonicus. Issue 6 (14th April 2021) - Aoki, Satoki; Aboshi, Takako; Onodera, Takumu; Kimura, Ken-ichi; Arai, Daisuke; Iizuka, Yoshiaki; Murayama, Tetsuya
ABSTRACT: Mushrooms of the Omphalotus genus are known to be rich in secondary metabolites. In the quest for new bioactive compounds, we analyzed the compounds isolated from the mycelium of the poisonous mushroom Omphalotus japonicus . As a result, a new polyisoprenepolyol, which was named omphaloprenol A, was identified, along with known substances such as hypsiziprenol A10 and A11, illudin S, and ergosterol. The chemical structure of omphaloprenol A was elucidated by nuclear magnetic resonance and infrared spectroscopies and mass spectrometry, and its bioactivity was investigated. Omphaloprenol A showed growth promoting activity against the root of lettuce seeds and cytotoxicity against HL60 cells. To the best of our knowledge, this is the first report on the isolation of a polyisoprenepolyol compound from Omphalotaceae mushrooms. Graphical Abstract: